L’affermazione del “localismo costituzionale in Italia": una nuova governance che a raccontarla non ci si crede. // The emergence of constitutional localism in Italy: a new governance beyond belief - Sclavi, Marianella; Lattuille, Stefania; Bertello, Agnese (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
"Localismo costituzionale” sta ad indicare un nuovo ethos civico e forma di governance che sposta il più grande numero possibile di decisioni pubbliche a livello di comunità, ancorandole direttamente al quadro di libertà e dei diritti garantiti dalla costituzione. Rietrano in questa categoria una moltitudine di iniziative dal basso, di cittadinanza attiva che si propongono di affrontare questioni di interesse comune, dalla rigenerazione di edifici e territori in crisi, alla fornitura di beni e servizi, promozione di forme di turismo “slow” o alternativo, ecc in modo partecipato e co-progettuale. La loro fioritura è in buona parte dovuta alla ormai palese incapacità delle strutture pubbliche tradizionali di gestire la complessità sociale e al riconoscimento che questo compito può essere meglio assolto favorendo la nascita e vitalità di organismi che vedono come protagonismo i diretti interessati. L’articolo descrive le tappe e gli sviluppi di questo cambiamento e ne sottolinea le dimensioni sovversive rispetto alla tradizionale concezione dei rapporti fra società civile e stato e fra iniziativa dei cittadini e “interesse generale”. Il nuovo modo di governance viene descritto attraverso due specifiche esperienze, una al nord del paese, le case di quartiere di Torino e una all’estremo sud, un'iniziativa che si è dimostrata vincente nell’affrancare i contadini sia dall’assoggettamento alla ‘ndrangheta, sia allo stozzinaggio dei monopoli della distribuzione dei prodotti. ENGLISH What is named “Constitutional localism” is a new civic ethos and form of governance that intend to shift the greatest number of public decisions possible to the community level - with a clear mission to promote locally the individual freedoms and rights guaranteed by the Constitution. A variety of initiatives and undertakings fall within this category, all run by groups of active citizens who address issues of the general good, like regeneration of abandoned buildings and public spaces, the creation of new job opportunities, giving birth to creative no profit or low profit economic initiatives like “slow tourism”, “social farming” and the diffusion of alternative energy plants and so on. All of them are managed in a participatory fashion through a transparent process open to the local dwellers. Their proliferation is due to the by now manifest failure of the public institutions to deal effectively with social complexity and to the recognition that this task can be carried out better by undertakings and associations run by the local stakeholders with the non- intrusive help (only if and when asked) of public operators and powers. This paper describes the main steps and developments of what is seen as a real paradigm shift in the forms of governance from bureaucracy to trans (o post) bureaucracy, from capitalism to trans (or post) capitalism. The new model of governance is more concretely highlighted through the illlustration of two specific experiences, one in the Nord part of the country, the “Neighborhood houses” in Turin and the other at the extreme South, an undertaking which succeded in helping the local farmers to cast themselves free from both the subjugation of the ‘ndrangheta and the loan sharking of the big monopoles of the distribution network. And by illustrating how these results are achieved, it shows that they are beyond the ways and goals normally attainable respectively by both the profit and public sector.